2008
DOI: 10.1111/j.1365-2958.2008.06298.x
|View full text |Cite
|
Sign up to set email alerts
|

The holin of bacteriophage lambda forms rings with large diameter

Abstract: Summary Holins control the length of the infection cycle of tailed phages (the Caudovirales) by oligomerizing to form lethal holes in the cytoplasmic membrane at a time dictated by their primary structure. Nothing is currently known about the physical basis of their oligomerization or the structure of the oligomers formed by any known holin. Here we use electron microscopy and single-particle analysis to characterize structures formed by the bacteriophage λ holin (S105) in vitro. In non-ionic or mild zwitterio… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

2
58
0

Year Published

2009
2009
2013
2013

Publication Types

Select...
8
2

Relationship

4
6

Authors

Journals

citations
Cited by 56 publications
(60 citation statements)
references
References 38 publications
(55 reference statements)
2
58
0
Order By: Relevance
“…This altered packing might allow much larger rafts to form before ion leakage leads to local depolarization. In addition, the behavior of purified S 21 68 and S105 in the nonionic detergent dodecylmaltoside supports the notion that the canonical holin has much more scope for protein-protein interactions (20). S105 was found to form highly oligomeric ring structures estimated to contain >70 molecules, whereas S 21 68 forms a heptameric homooligomer in dodecylmaltoside (4).…”
Section: Discussionsupporting
confidence: 51%
“…This altered packing might allow much larger rafts to form before ion leakage leads to local depolarization. In addition, the behavior of purified S 21 68 and S105 in the nonionic detergent dodecylmaltoside supports the notion that the canonical holin has much more scope for protein-protein interactions (20). S105 was found to form highly oligomeric ring structures estimated to contain >70 molecules, whereas S 21 68 forms a heptameric homooligomer in dodecylmaltoside (4).…”
Section: Discussionsupporting
confidence: 51%
“…Using electron microscopy and recombinant proteins purified in nonionic detergent, Savva (et al 2008) found that functional S105 formed multimeric ring structures, which likely reflect a minimum energy arrangement in the membrane. In addition, recent cryo-electron microscopy and tomography studies revealed that the lesions caused by holin S105 of phage l could be visualized as interruptions in the bilayer spanning very large areas of the cytoplasmic membrane, averaging >350 nm in diameter (Dewey et al 2010).…”
Section: Active Bax and Bak As Functional Holins Mechanistically Linmentioning
confidence: 99%
“…S 21 68 his , S 21 68⌬TMD1 his , and irsS 21 68 his were purified from an induced culture of E. coli C43(DE3) (28), carrying the plasmid pETS 21 68 his , pETS 21 68⌬TMD1 his , and pETirsS 21 68 his , respectively. Induction, detergent extraction, and purification of the his-tagged proteins by immobilized metal affinity chromatography have been described (29) and can be found in SI Materials and Methods. S 21 68 his and its variants were eluted in buffer containing 20 mM Tris, pH 7.9/150 mM NaCl/500 mM imidazole/0.1% (wt/vol) DDM.…”
Section: Purification and Gel Filtration Chromatography Of S 21 68 Himentioning
confidence: 99%